STRATEGI SEKOLAH UNTUK MENINGKATKAN PESERTA DIDIK BARU BERBASIS AGAMA KRISTEN (STUDI SMA SWASTA DI SURABAYA) - Maruta Pradana, Ramadhan; Murtadlo, Murtadlo; Wulandari, Ayu (Dharmas Education Journal (DE_Journal), 2025)
The development of many private schools in Surabaya has resulted in increasingly tight competition for students between schools. The aim of this research is to look at the strategies of Christian-based private schools in Surabaya in improving the quality and quantity of new students. The methodology used in this research uses qualitative case studies, data collection in this research is by means of interviews, observation, documentation and questionnaires. This research took 1 Christian-based private school in Surabaya. The subjects of this research were the principal, deputy principal, teachers, and parents/committee. The results of this research contain 3 major sub-themes, including, (1) Implementation of internal strategies in line with human resource development and encouragement to introduce schools, improving infrastructure, student services, superior Christian-based curriculum, strong organizational coordination, development of science and technology, Internal policies that provide benefits for prospective students. (2) Implementation of External Strategy, the role of participation by parents, alumni and the surrounding community, central government education policies, and development of creative educational marketing implementation. (3) Obstacles in implementing the strategy require developing facilities and improving services for new students that need to be improved following current developments. Implementing an external strategy requires strategic marketing efforts and price competition that is in line with school financing.